Validation of inducible basophil biomarkers: Time, temperature and transportation. Issue 6 (4th February 2021) - Kim, Theodore; Yu, Jing; Li, Henry; Scarupa, Mark; Wasserman, Richard L.; Economides, Athena; White, Martha; Ward, Carla; Shah, Atul; Jones, Douglas; Rathkopf, Melinda; Frye, Kelly; et al.
Abstract: Background: The short stability window of several hours from blood collection to measuring basophil activation has limited the use of flow cytometry‐based basophil activation assays in clinical settings. We examine if it is possible to extend this window to 1 day allowing for shipment of samples between laboratories. Several options exist for reporting the results including reporting all the measured values directly, calculating ratios and reporting a single value covering all measured results. Each of these options have different stability and value to the physician. Methods: Whole blood samples from peanut allergic patients were stimulated with four different peanut concentrations at Day 0, Day 1, and Day 2. Samples were stored under temperature‐controlled conditions. Flow cytometry was used to analyze the samples. The basophil activation and degranulation were measured as percentage of positive CD63 basophils and CD203c MFI fold change. Shipped samples were transported under ambient conditions. Results: The results show that CD63 is a stable marker at Day 1. The CD203c ratio decreases significantly at Day 1. Calculating the CD63/IgE ratio proves to be more stable than CD63 alone. The most stable readouts are the semi‐quantitative results and the trajectory of the dose response curve. Finally, we confirmed that the stability can be extended to samples shipped overnight to the laboratory. Conclusions: It is possible to extend the stability of the basophil activation assay to 1 day for samples stored at 18–25°C as well as samples shipped under ambient conditions as long as the temperature is within the 2–37°C range.